2014
DOI: 10.19030/jber.v12i2.8522
|View full text |Cite
|
Sign up to set email alerts
|

Human Asset Accounting And Measurement: Moving Forward

Abstract: Changes in the accounting profession and in the way

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…Human capital accounting is indeed, a highly complex process and this complexity principally lies in the reality that there are hundreds of factors, which comprise an employee's value [1]. Nevertheless, let us properly commence this conceptual elucidation from the possible meaning of human capital.…”
Section: Conceptual Elucidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human capital accounting is indeed, a highly complex process and this complexity principally lies in the reality that there are hundreds of factors, which comprise an employee's value [1]. Nevertheless, let us properly commence this conceptual elucidation from the possible meaning of human capital.…”
Section: Conceptual Elucidationmentioning
confidence: 99%
“…Human capital accounting, human asset accounting and human resource accounting are all synonymous concepts. Indeed, some authors [1,9] use these concepts interchangeably. In this study however, our choice of concept is human capital accounting.…”
Section: Conceptual Elucidationmentioning
confidence: 99%
“…It is important to examine factors that contribute to an employee's productivity. These factors fall into several different categories, each important in their own way (Stanko, Zeller, & Melena, 2014).…”
Section: One Of the Unresolved Issues In Human Resourcementioning
confidence: 99%
“…Doing so would represent arguably the most monumental finding in the history of financial accounting, but until a reliable measure to report human capital is established, the Financial Accounting Standards Board cannot issue mandate that companies should report that valuable information. Such an action so would only produce inaccurate information leading to misguided decisions (Stanko, Zeller, & Melena, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…This benefit or cost is related to non financial impact. (Brian, Thomas, & Matthew, 2014) found that human resources are capital because it adds value to organization and this value of human resource should be shown in the financial report.…”
Section: Importance and Measured Of Human Resources Accountingmentioning
confidence: 99%